Two new genus-group replacement names of Riodinidae from Asia (Lepidoptera, Papilionoidea, Riodinidae) - Huang, Si-Yao; Inayoshi, Yutaka; Espeland, Marianne (Zootaxa, 2024)
Two new replacement names for two genus-group taxa are proposed: Spitosa Espeland, Huang & Inayoshi, nom. nov. for Sospita Hewitson, 1861 and Sibosia Espeland, Huang & Inayoshi, nom. nov. for Sosibia Fruhstorfer, 1914. Both taxa are compared with Abisara C. Felder & R. Felder, 1860. The adult and genitalia of the type species of Spitosa, Sibosia and Abisara are illustrated and compared. Checklists for Spitosa and Sibosia are provided.